Verification and validation of CFD models and dynamic similarity for fluidized beds - Grace, John R.; Taghipour, Fariborz (Powder technology, 2004)
Claims and suggestions in the literature that verification or validation of CFD numerical models has been achieved for fluidized beds are shown to be inconsistent with objective criteria and accepted usage of terminology. Verification involves confirming the accuracy of the computational aspect of the model, for example by comparing results against known solutions, something that is virtually impossible in dense multiphase systems, except for trivial cases. Validation requires objective consideration of computational and numerical error, as well as comparison of model predictions and experimental data over broad ranges of conditions. More care is required in applying these terms, and in planning and conducting experiments to test the validity of fluidized bed numerical codes. Similar considerations apply to experimental attempts to confirm the completeness of sets of matched dimensionless groups used for dynamic scaling of multiphase systems.